Enforcement of Choice of Court Agreements Granting International Jurisdiction to Albanian Courts - Flutura Kola Tafaj; Silvana Cinari (LeXonomica, 2023)
This paper aims to critically analyse the formal and substantive validity of choice of court agreements in favour of Albanian courts. The provisions of the Albanian Private International Law and their implementation by Albanian courts are in the focus. However, considering that the Albanian Private International Law provisions are approximated with the EU acquis communautaire and since the provisions on choice of courts agreements are drafted in terms that are fully compatible with the Council Regulation 44/2001 of December 22, 2000 "On Jurisdiction, Recognition and Implementation of Judicial Decisions in Civil Matters and Trade” (Brussels I Regulation), the interpretation of the Albanian law provisions is also done in the light of the case law of the Court of Justice of the European Union. After a thorough analysis of the Albanian Private International Law provisions concerning choice of court agreements and of the Albanian case law, the paper concludes that they are not always interpreted and applied correctly and that the rich case law of the Court of Justice of the European Union can provide valuable guidance.PovzetekNamen tega prispevka je kritično analizirati formalno in vsebinsko veljavnost sporazumov o izbiri sodišča v korist albanskih sodišč. V ospredju so določbe albanskega mednarodnega zasebnega prava in njihovo izvajanje s strani albanskih sodišč. Ker pa so določbe albanskega mednarodnega zasebnega prava približane pravnemu redu EU in ker so določbe o sporazumih o izbiri sodišča oblikovane tako, da so v celoti skladne z Uredbo Sveta 44/2001 z dne 22. decembra 2000 „O pristojnosti, priznavanju in izvajanju sodnih odločb v civilnih in gospodarskih zadevah“ (Uredba Bruselj I), je razlaga določb albanskega prava opravljena tudi ob upoštevanju sodne prakse Sodišča Evropske unije. Po temeljiti analizi določb albanskega mednarodnega zasebnega prava o sporazumih o izbiri sodišča in albanske sodne prakse članek ugotavlja, da se te določbe ne razlagajo in uporabljajo vedno pravilno ter da lahko bogata sodna praksa Sodišča Evropske unije zagotovi dragocene smernice.